Phenotypic age mediates the associations between platelet-to-lymphocyte ratio and all-cause and cause-specific mortality: A prospective cohort study - Xiangjun Li; Jia Wang; Mengqi Zhang; Yujing Li; Xiaoxuan Li; Jiaqi Zhang; Lihua Zhang; Yixuan Zhang; Zhenkang Qiu (Heliyon)
Objectives: The platelet-to-lymphocyte ratio (PLR) is a novel indicator of inflammation, but research on the links and mechanisms between the PLR and long-term health conditions is lacking. This study aimed to evaluate the relationship between phenotypic age (PhenoAge) mediated PLR and mortality among US adults. Methods: A total of 37,182 participants from the National Health and Nutrition Examination Survey (NHANES) database (1999–2018) were included to evaluate the PLR's relevance to survival by Cox regression models. The associations between the PLR and mortality were apparent using restricted cubic spline regression. Mediation analyses were conducted to investigate the mediated effects of PhenoAge on the associations of PLR with mortality. Results: Compared to the PLR in Quintile 1 participants, the multivariable-adjusted Cox model showed the PLR in Quintile 5 was linked with greater risks of death from all-cause (HR, 1.14; 95 % CI: 1.04–1.25), cardiovascular disease (CVD) (HR, 1.26; 95 % CI: 1.01–1.57) and respiratory disease (HR, 1.98; 95 % CI: 1.35–2.90). The risk of death from cancer was approximately 28 % lower for participants with the PLR in the fourth quintile. Restricted cubic splines showed the U-shaped relationships between PLR and all-cause and cancer mortality, and the positively linear relationships between PLR and cardiovascular disease (CVD) and respiratory mortality. Moreover, mediation analysis revealed that PhenoAge partially mediated 45.33 %, 44.26 %, and 15.35 % of the associations of PLR with all-cause, CVD, and respiratory disease mortality, respectively. Conclusion: The PLR, a valuable index that should be recommended for use, was independently linked with all-cause and cause-specific mortality, with PhenoAge playing a partial mediating role in the relationships.